2017
DOI: 10.1186/s40359-017-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived racism on psychological distress mediated by venting and disengagement coping in Native Hawaiians

Abstract: BackgroundStudies have linked perceived racism to psychological distress via certain coping strategies in several different racial and ethnic groups, but few of these studies included indigenous populations. Elucidating modifiable factors for intervention to reduce the adverse effects of racism on psychological well-being is another avenue to addressing health inequities.MethodsWe examined the potential mediating effects of 14 distinct coping strategies on the relationship between perceived racism and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…However, other studies also found that higher levels of venting after discriminatory experiences led to higher psychological distress (43,91).Venting one's anger does not seem to help regulating negative emotions after ethnic discrimination, but rather seems to result in a prolongation of those negative emotions (113). Our findings also suggest that behavioral disengagement after discriminatory events did not lead to effective stress management, which is consistent with other findings in this context (43,114). It is assumed that behavioral disengagement was an indicator of learned helplessness (115), which could mean that victims of discrimination "gave up" or withdrew from actively dealing with stressors.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…However, other studies also found that higher levels of venting after discriminatory experiences led to higher psychological distress (43,91).Venting one's anger does not seem to help regulating negative emotions after ethnic discrimination, but rather seems to result in a prolongation of those negative emotions (113). Our findings also suggest that behavioral disengagement after discriminatory events did not lead to effective stress management, which is consistent with other findings in this context (43,114). It is assumed that behavioral disengagement was an indicator of learned helplessness (115), which could mean that victims of discrimination "gave up" or withdrew from actively dealing with stressors.…”
Section: Discussionsupporting
confidence: 86%
“…Possibly, everyday discrimination is less specific with regard to applied coping strategies than other forms of ethnic discrimination. The number of significant coping strategies in our assessment of active and passive harm was, however, similar to other studies that used the Brief COPE (43,91). The effects of discrimination on stress in our sample occurred largely (passive harm, everyday discrimination) or entirely (active harm) through indirect effects, and these associations remained after holding age and sex constant.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations